2023
DOI: 10.1021/acs.analchem.3c00091
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Chromatography–Mass Spectrometry Analysis of Frataxin Proteoforms in Whole Blood as Biomarkers of the Genetic Disease Friedreich’s Ataxia

Abstract: Friedreich’s ataxia (FRDA) is caused primarily by expanded GAA repeats in intron 1 of both alleles of the FXN gene, which causes transcriptional silencing and reduced expression of frataxin mRNA and protein. FRDA is characterized by slowly progressive ataxia and cardiomyopathy. Symptoms generally appear during adolescence, and patients slowly progress to wheelchair dependency usually in the late teens or early twenties with death on average in the 4th decade. There are two known mature proteoforms of frataxin.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 43 publications
1
16
0
Order By: Relevance
“…These studies have measured frataxin in fibroblasts, lymphocytes, muscle biopsies (35), buccal cells, peripheral blood ( 36, 37 ) and platelets (29, 38). These studies have shown that frataxin levels in peripheral tissues ranges from 30% to 40% of control levels in FRDA patients and from 60 to 80% of control levels in FRDA carriers ( 39-42 ). As we have observed similar differences between the three groups, we can conclude that the results obtained are accurate.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have measured frataxin in fibroblasts, lymphocytes, muscle biopsies (35), buccal cells, peripheral blood ( 36, 37 ) and platelets (29, 38). These studies have shown that frataxin levels in peripheral tissues ranges from 30% to 40% of control levels in FRDA patients and from 60 to 80% of control levels in FRDA carriers ( 39-42 ). As we have observed similar differences between the three groups, we can conclude that the results obtained are accurate.…”
Section: Discussionmentioning
confidence: 99%
“…While there are currently no curative treatments for the cardiac manifestations of FRDA, numerous therapeutic approaches are being tested in pre-clinical models 9 11 As FRDA is a genetic disease caused by an autosomal recessive mutation in the frataxin gene ( FXN ) that encodes the highly conserved frataxin protein (FXN), genetic approaches for treatment are under investigation 12 14 . FRDA-related mutations classically consist of a trinucleotide (GAA) repeat expansion within the first FXN intron, which results in DNA triplex formation, epigenetic silencing, and consequently reduced FXN protein production 15 17 . While the intracellular role of FXN has not been clearly defined 18 , 19 , FXN deficiency compromises iron-sulfur (Fe-S) cluster biosynthesis, leading to mitochondrial iron overload, mitochondrial dysfunction, and oxidative stress 20 that can culminate in the neuro- and cardio-degeneration characteristics of FRDA 21 24 .…”
Section: Introductionmentioning
confidence: 99%
“…Gene replacement (e.g., gene therapy) represents a promising approach to treating FRDA 10 , 11 . One of the pivotal challenges critical to the success of gene therapy is to induce sufficient FXN protein expression to achieve therapeutic efficacy while limiting the toxicity induced by its overexpression, which can result in impaired Fe-S biogenesis and cellular/mitochondrial function, and eventually lead to cell death 17 . Previous gene therapy studies conducted in mouse models have shown mature hFXN expression at levels that cause cardiotoxicity and hepatotoxicity, leading to reduced efficacy 25 , 26 .…”
Section: Introductionmentioning
confidence: 99%
“…This is because the active form of FXN is not detectable in serum or plasma; it predominantly resides in erythrocytes 8 . A novel technique utilizing stable isotope dilution Liquid Chromatography-Mass Spectrometry to target the isoform E of FXN from whole blood has been developed 8,10 . However, questions remain regarding its cost-effectiveness, and it is mainly used to assess the efficacy of interventions that aim to increase FXN levels.…”
Section: Introductionmentioning
confidence: 99%